Pengaruh Penggunaan Total Hutang Total Modal Total Penjualan terhadap Perolehan Laba Bersih pada Industri Makanan dan Minuman yang Terdaftar di BEI Periode 2013-2017 - Nurhikmah Nurhikmah (Science of Management and Students Research Journal (SMS), 2019)
This study aims to analyze whether the total debt total capital of total sales has a partially or simultaneously significant effect on net income in the food and beverage industry listed on the IDX for the period 2013-2017. This research uses quantitative descriptive analysis method and qualitative descriptive analysis. The analysis tool of this study is the same as the analytical method, namely multiple linear regression using log. The results of the study show that simultaneously from this study shows the effect of total total capital total debt usage on net income in the food and beverage industry listed on the IDX for the period 2013-2017. Simultaneously with the number of Fc 154.741 and Ftable 2.91, it can be seen that Fcount> Ftable is 154.741> 2.91, meaning that there is a significant effect on gross profit margin, earnings per sahre and debt tototal assets ratio to net income. Partial influence on the effect of total total capital total debt sales on Net Profit in the Food and Beverage Industry listed on the Stock Exchange for the period 2013-2017 with total debt (-0.7773) and ttable 2.039 means tcount <ttable, (-0.77) <2,039, meaning total debt does not have a positive effect on net income, total capital is 10.360 and ttable 2.039 means tcount> ttable, 10.360> 2.039, meaning that total capital does have a positive influence on net income and total sales tcount (-0.926) and ttable 2.039 is the meaning of tcount <t table, (-0,926) <2,039 which means that total sales do not have a positive effect on net income for the period 2013-2017. Keywords: Total Debt, Total Capital, Total Sales, Net Profit.